ANALYSIS OF PARTICIPATION IN QUALITY MANAGEMENT OF "UZ AUTO MOTORS" IN THE PROCESS OF DIGITAL TRANSFORMATION - Abdullaev Muzaffar Abdujabbarovich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
Active participation of the company in quality management is one of the main principles of management. For this, employees at all levels form the basis of the company and their active participation in the company's activities, and the use of their talents, can be the main ground for development.